Dark count rate and band to band tunneling optimization for single photon avalanche diode topologies. (June 2019) - Haddadifam, Taha; Azim Karami, Mohammad
Abstract : This paper proposes two optimal designs of single photon avalanche diodes (SPADs) minimizing dark count rate (DCR). The first structure is introduced as p + /pwell/nwell, in which a specific shallow pwell layer is added between p + and nwell layers to decrease the electric field below a certain threshold. The simulation results show on average 19.7% and 8.5% reduction of p + /nwell structure's DCR comparing with similar previous structures in different operational excess bias and temperatures respectively. Moreover, a new structure is introduced as n + /nwell/pwell, in which a specific shallow nwell layer is added between n + and pwell layers to lower the electric field below a certain threshold. The simulation results show on average 29.2% and 5.5% decrement of p + /nwell structure's DCR comparing with similar previous structures in different operational excess bias and temperatures respectively. It is shown that in higher excess biases (about 6 volts), the n + /nwell/pwell structure is proper to be integrated as digital silicon photomultiplier (dSiPM) due to low DCR. On the other hand, the p + /pwell/nwell structure is appropriate to be utilized in dSiPM in high temperatures (above 50 °C) due to lower DCR value.